Comparison of Carbon Dioxide Laser Modalities for Removal of Polymethylmethacrylate Cement - Lange, D. N.; Rochat, M. C.; Bartels, K. E.; Payton, M. E.; Hoffman, R. J.; Schafer, St. A.; Dickey, D. Th. (Veterinary and Comparative Orthopaedics and Traumatology, 1997)
Polymethylmethacrylate (PMMA) cement is routinely used in a number of surgical procedures performed on human beings and animals. As the use of PMMA increases in veterinary medicine, the need for its removal during “revision” surgeries also increases. Common indications for removal of PMMA are infection, aseptic loosening, and fracture of the cement. Polymethylmethacrylate cement is often applied in areas of the body where typical mechanical methods of removal are dangerous or impossible. Cement placed near the spinal canal for the treatment of caudal cervical malformation-malarticulation syndrome or deep within the femoral medullary canal for total hip prostheses are examples. The ability to safely and easily remove cement should lower intraoperative complication rates associated with revision surgeries.The vaporization efficiency for removal of PMMA cement for three carbon dioxide laser modalities (continuous wave only, with Swift-Lase™ attachment, and with Fiberlase™ wave guide) were determined, as well as heat transferred to periosteal surface during PMMA cement vaporization, and gross pathology to the cortical bone at the maximum vaporization efficiency power. Cefazolin sodium was added to half of the samples to determine if the ablation ablation rate of PMMA would be affected. The C02 laser with wave guide was the most efficient modality for vaporization at 25 watts, and produced significantly less heat transfer to the periosteal surface than the heat of polymerization of the PMMA cement. Cefazolin sodium appeared to slightly decrease the vaporization efficiency, and all of the lasers produced gross and histologic lesions to the bone.Three laser types were compared for their ability to efficiently and safely remove polymethylmethacrylate (PMMA) cement. Vaporization rates were determined. The most efficient wattage for each laser modality was used to compare the heat transferred during PMMA removal as well as the pathology created by application of each laser modality to the cortical bone. The CO2 laser with wave guide at 25 watts was the most efficient modality for vaporization of PMMA cement, and produced significantly less heat transfer to the periosteal surface than the CO2 laser and the CO2 laser with Swift-Lase™.
Keywords: Carbon dioxide laser; polymethylmethacrylate; cortical bone